Three transition-metal complexes with the macrocyclic ligand meso-5,7,7,12,14,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane (L): [Cu(ClO4)2(L)], [Zn(NO3)2(L)] and [CuCl(L)(H2O)]Cl - Yasmin, Sabina; Suarez, Sebastian; Doctorovich, Fabio; Roy, Tapashi G.; Baggio, Ricardo Fortunato (Wiley Blackwell Publishing, Inc, 2013)
Fil: Yasmin, Sabina. University of Chittagong; Bangladesh